DAYA SAING EKOWISATA BERKELANJUTAN TAMAN NASIONAL BROMO TENGGER SEMERU - Joshi Maharani Wibowo; Sri Muljaningsih; Dias Satria (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Bromo Tengger Semeru National Park (BTSNP) is one of the conservation areas in Indonesian that functions as a protected area, a biosphere reserve area, and a tourism destination. The research was conducted to determine the BTSNP sustainable competitiveness potential as a tourism destination as well as conservation area. This research used secondary data obtained from the TripAdvisor site in 2018 and primary data obtained through interviews, FGD, documentation, and observation. The data was analyzed by using a sentiment analysis approach based on the Travel and Tourism Competitiveness Index (TTCI) concept. The result showed that BTSNP’s sustainable competitiveness was most negatively influenced by tourism policy and environmental conditions. To overcome those of negative impacts, the related stakeholders need to apply more suitable policies based on natural and social condition of BTSNP, such as biosphere reserve and local tourism clustering-based policy. The purpose of developing a new local tourism attraction (clustering) in BTSNP was to overcome waste and excess tourist capacity in the BTSNP protected area. The clustering also aims to maximize local tourism development strategies based on the biosphere reserve concept in the BTSNP area. So, the policies related to biosphere reserve and tourism clustering can effectively increase sustainable competitiveness ecotourism in BTSNP.